High-dose amoxicillin should be included in the empirical treatment of suspected meningitis in patients at risk of HIV infection. (12th May 2011) - Talbot, Ben Edward Michael; Webster, Daniel; Fisher, Martin; Alexander, Eliza
Abstract : The authors report on a case of Listeria rhomboencepahlitis in a previously undiagnosed HIV positive man. This case is of interest as the incidence of Listeria has increased dramatically in recent years and so may increase in the HIV-infected population. The organism is inherently resistant to cephalosporin antibiotics, empirically employed in the treatment of central nervous system infections and thus highlights the need to include amoxicillin in meningitis treatment regimes in patients at risk of HIV infection as well as the older and those known to be immuno-compromised.